2020
DOI: 10.3390/ma13214759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Nanocellulose Loaded with Curcumin and Its Degradation Products on Human Dermal Fibroblasts

Abstract: Bacterial nanocellulose has found applications in tissue engineering, in skin tissue repair, and in wound healing. Its large surface area enables the adsorption of various substances. Bacterial nanocellulose with adsorbed substances can serve as a substrate for drug-delivery of specific bioactive healing agents into wounds. In this study, we loaded a bacterial nanocellulose hydrogel with curcumin, i.e., an important anti-bacterial and healing agent, and its degradation products. These products were prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…BNC has the advantages of a large surface area, high porosity, ease of sterilization, excellent tensile strength, and good biocompatibility, and has been used in tissue engineering, skin tissue repair, and wound healing. Zikmundova et al [ 18 ] reported the BNC could not only enhance the solubility and the penetration of the anti-bacterial and healing agent curcumin when prepared at a high temperature, it could also reduce the cytotoxic of curcumin for human dermal fibroblasts and enhanced the antibacterial activity. Not only that, studies have shown that the microenvironment is not limited to a low pH of the bacterial infection lesion and biofilm makes it possible to design a smart targeted and responsive nanocarrier for antimicrobial therapy [ 19 , 20 ].…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%
“…BNC has the advantages of a large surface area, high porosity, ease of sterilization, excellent tensile strength, and good biocompatibility, and has been used in tissue engineering, skin tissue repair, and wound healing. Zikmundova et al [ 18 ] reported the BNC could not only enhance the solubility and the penetration of the anti-bacterial and healing agent curcumin when prepared at a high temperature, it could also reduce the cytotoxic of curcumin for human dermal fibroblasts and enhanced the antibacterial activity. Not only that, studies have shown that the microenvironment is not limited to a low pH of the bacterial infection lesion and biofilm makes it possible to design a smart targeted and responsive nanocarrier for antimicrobial therapy [ 19 , 20 ].…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%
“…The cytotoxicity of bacterial nanocellulose (BNC) was evaluated by Zikmundova et al [ 191 ] on a bacterial nanocellulose hydrogel loaded with curcumin and its degradation products (DC: vanillin, tumerone, and feruloylmethane), in view of the potential application in wound dressing. In vitro tests performed on human dermal fibroblasts revealed that the cytotoxicity of the materials depended strongly on the concentration of the antibacterial agents and that the degradation products of curcumin are more cytotoxic than pure curcumin.…”
Section: Toxicological Evaluation and Potential Limitations Of Ncs-based Materialsmentioning
confidence: 99%
“…BNC serves as an efficient drug delivery system for bioactive compounds due to its mechanical attributes, biocompatibility, adsorption capacity, and delivery efficiency [ 2 ]. It has also been utilized for encapsulating natural extracts, such as curcumin, to enhance their bioavailability [ 3 , 4 ]. Notably, BNC has received recognition as a safe substance by the USA Food and Drug Administration (FDA) since 1992 and has found applications as a dietary fiber [ 5 , 6 ], food additive, and food substitute, offering benefits such as reduced calorie and fat intake, improved formulation viscosity and stability, and reduced moisture loss from food products [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, a biopolymer derived from partial deacetylation of chitin, has surfaced as a mucoadhesive [ 12 ]. Comprising 2-acetamide-2-deoxy-β- d -glucose and 2-amine-2-deoxy-β- d -glucose units [ 7 , 13 ], chitosan stands out for its biocompatibility, biodegradability, and ability to generate mucoadhesion via its positive surface charge [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation